Store Layout and Purchase Intention: Unraveling a Complex Nexus on Indonesian Minimarket - Elkana Timotius; R Dimas Widya Putra (Universitas Mercu Buana, 2023)
Objectives: The store layout in a minimarket is a strategy to encourage repeat purchases from customers. This study attempts to assess the layout design of the minimarket in Indonesia and comprehend its contribution to purchase intention.Methodology: This research observed two well-known minimarkets in Indonesia, namely Alfamart and Indomaret. A literature review associated with field findings was conducted to find their relationship to consumer purchase intention.Finding: Consumers' shopping behavior in minimarket retail stores in Indonesia does not show much difference from the behavior of consumers in other countries. Consumers will not linger in a store that is generally not too large. They come to minimarket retail stores not for